Chronic heart failure with preserved ejection fraction: optimal therapy. Literature review - A. A. Kuzmenko; A. A. Sokolova; D. A. Napalkov (Сеченовский вестник)
The literature review discusses approaches to the treatment of patients with chronic heart failure and preserved ejection fraction (EF>50) – HFpEF. The impact of various groups of drugs on the prognosis and quality of life of patients in this cohort was assessed based on the results of randomized trials, systematic reviews and meta-analyses, clinical recommendations of recent years. To date, only sodium-glucose cotransporter-2 inhibitors unequivocally improve the quality of life and prognosis of patients with HFpEF. Angiotensin receptor – neprilysin inhibitors and mineralocorticoid receptor antagonists are effective in terms of prognosis and quality of life only in patients with HFpEF in combination with resistant hypertension. In patients with sinus rhythm, heart rate > 70 beats/min and concomitant coronary artery disease, a combination of bisoprolol and ivabradine may be considered. Diuretics are recommended for patients with HFpEF when there are signs of congestion and signs of decompensation. Other groups of drugs do not significantly affect the quality of life and prognosis of patients with HFpEF and can be prescribed to such patients only as part of planned therapy for the treatment of other concomitant cardiovascular diseases.